God, Religion and History: The Significance of Schelling’s Philosophy of Religion for Determining the Concept of Religion - Christian Danz (Religions, 2024)
This article discusses Schelling’s contribution to the definition of the concept of religion in post-Kantian philosophy. In three lines of argument, it is shown that Schelling’s late lectures on the philosophy of mythology and revelation place religion in a history of development in which religion is successively understood as religion. Schelling assumes that religion is independent of reason and is based on a real relationship with God that is connected to the nature of man. This makes the philosophy of religion an independent academic discipline. Schelling links the historical development of religion and the history of God in his concept of monotheism. This is the content of Schelling’s formula that God is the Lord of being.